The Dissemination of the EFQM Self-evaluation Model across Europe - Erlantz ALLUR (Revista de Management Comparat International)
This article analyzes the diffusion process of the Total Quality Management (TQM) paradigm, and, more specifically, evaluates the diffusion process of the EFQM model, one of the most successful self-evaluation models for TQM all over the world. The work refers to the major level of dissemination achieved by this self-evaluation model across Europe, although their unequal dissemination is also stressed. A clear predominance of countries with disparate market structure and institutional environment, such as U.K., Spain, Germany, Italy and Turkey, is pointed out. The conclusions drawn in the article may be of interest both for academic and professional spheres of activity but, overall, for public-devisors.